(untitled) (Baghdad Science Journal, 2015)
Single-input Multiple-output Signals Third-order Active-R Filter for different Circuit Merit Factor Q Configuration is proposed. This paper discusses a new configuration to realize third-order low pass, band pass and high pass. The presented circuit uses Single-input Multiple-output signals, OP-AMP and passive components. This filter is useful for high frequency operation, monolithic IC implementation and it is easy to design .This circuit gives three filter functions low-pass, high-pass and band-pass. This filter circuit can be used for different merit factor (Q) with high pass band gain. This gives better stop-band attenuation and sharper cut-off at the edge of the pass-band. Thus the response shows wider pass-band. The Ideal value of this filter circuit which is closed to Ideal value of third-order active-R filter is at 0.8? Q ?6. The advantages of this circuit are reduction in size and weight, increased circuit reliability, more economical and easy for manufacturing.